Bluetooth profiles the definitive guide - Gratton, Dean A. (Prentice Hall, 2003)
Bluetooth Profiles are the key to delivering interoperable products that work reliably, "right out of the box." Now, leading Bluetooth expert Dean Anthony Gratton brings the Bluetooth Profiles to life, showing you exactly how to use them to build winning user-centered products. Gratton takes you "under the hood" of every significant Bluetooth Profile, from Bluetooth's essential Foundation Profiles to powerful emerging profiles for personal area networking, automotive applications and imaging. Drawing on his extensive experience with Bluetooth development, Gratton also offers practical guidance for creating innovative new profiles of your own.